Effect of Mathematics Teachers’ Problems in Teaching Equation, Figure, Drawing Symbols and Use of Software on Mathematical Content Instruction - Joshi, Dirgha Raj; Sharma Chapai, Krishna Prasad; Khanal, Bishnu (Journal of Fine Arts Campus, 2022)
The aim of the research was to measure the effect of mathematics teachers’ problems in teaching equation and figure, drawing symbols, and use of software on the problems of mathematical content instruction online with respect to educational background and ICT training status. The cross-sectional online survey design was used among 258 secondary level mathematics teachers of Nepal. The path analysis technique was used to analysis the data. The finding of the research shows that the problems in using software and drawing figures are main predictors to the problems in instructing mathematical content with respect to non-educational background and untrained in ICT teachers. Whereas the problems in drawing symbols and teaching equations are main predictors in mathematical content instruction with respect to educational background and trained in ICT teachers.